Appetitive traits and body mass index in Chinese adolescents: An 18-month longitudinal study with latent growth curve analyses. Issue 1 (January 2023) - Cheng, Yawei; Barnhart, Wesley R.; Liang, Guangsheng; Chen, Gui; Lu, Tom; He, Jinbo
Abstract: A longitudinal approach with Latent Growth Curve Modeling (LGCM) was adopted to explore the trajectories of appetitive traits corresponding to BMI in Chinese adolescents. Within a large sample of adolescents ( N = 2566, 45.9% boys) aged from 11 to 17 years ( M = 13.80, SD = 1.56) at the baseline survey, our results indicated that appetitive traits of emotional overeating, food fussiness, and hunger increased significantly over time while enjoyment of food decreased over time. Slowness in eating and satiety responsiveness significantly increased in girls, while emotional undereating significantly decreased in boys. Moreover, the growth parameters of emotional undereating and satiety responsiveness were significantly and negatively related to BMI in girls. Our findings evidence that certain appetitive traits could change over time in adolescence and these changes relate to weight status. Gender differences are suggested in the design of future intervention and treatment of overweight/obesity in Chinese adolescents.